Cerberus is a feedback inhibitor of Nodal asymmetric signaling in the chick embryo - Tavares, Ana Teresa (2018)
The TGF-beta-related molecule Nodal plays an essential and conserved role in left-right patterning of the vertebrate embryo. Previous reports have shown that the zebrafish and mouse Cerberus-related proteins Charon and Cerberus-like-2 (Cerl-2), respectively, act in the node region to prevent the Nodal signal from crossing to the right side, whereas chick Cerberus (cCer) has an unclear function in the left-side mesoderm. In this study, we investigate the transcriptional regulation and function of cCer in left-right development. By analyzing the enhancer activity of cCer 5' genomic sequences in electroporated chick embryos, we identified a cCer left-side enhancer that contains two FoxH1 and one SMAD binding site. We show that these Nodal-responsive elements are necessary and sufficient for the activation of transcription in the left-side mesoderm. In transgenic mouse embryos, cCer regulatory sequences behave as in chick embryos, suggesting that the cis-regulatory sequences of Cerberus-related genes have diverged during vertebrate evolution. Moreover, our findings from cCer overexpression and knockdown experiments indicate that cCer is a negative-feedback regulator of Nodal asymmetric signaling. We propose that cCer and mouse Cerl-2 have evolved distinct regulatory mechanisms but retained a conserved function in left-right development, which is to restrict Nodal activity to the left side of the embryo.